Remote sensing in urban sprawl modeling: Challenges and way forward in urban planning in Malaysia - Hj. Mohd. Noor, Norzailawati; Hashim, Mazlan (2009)
The theory of mathematics and modeling has long been introduced in the field of urban planning. Specifically modeling which was earlier introduced has started to develop by late 1960s. Modeling was used in various planning specialization such as economics, transportation, urbanization, ecology, and others. Remote Sensing application was also used informally in urban planning field concomitant with the launching of Landsat satellite in 1972. However, modeling which involves remote sensing in urban sprawl specialization in planning has only demonstrated its drastic development in early 1990s. Apart from monitoring, control and mapping of urban sprawl, remote sensing is combined with other application such as GIS and other urban planning parameters. Studies have also shown that remote sensing application is very flexible and is suitable with the ever changing and dynamic character of an urban system. The consistency in the remote sensing system that is able to track down any movement in land uses in a stipulated time gives aptness for the development of remote data sources and problems that arises in urbanization currently; subsequently giving a positive way forward for decision maker especially urban planners in Malaysia.